Impact of submesoscale processes on dynamics of phytoplankton filaments. Issue 3 (27th March 2015) - Shulman, Igor; Penta, Bradley; Richman, James; Jacobs, Gregg; Anderson, Stephanie; Sakalaukus, Peter
Abstract In Monterey Bay, CA, during northwesterly, upwelling favorable winds, the development of a southward flowing cold jet along the entrance to the Bay is often observed. This dense cold jet separates warm waters of the anticyclonic circulation offshore from the water masses inside the Bay. Interactions between the cold jet and the offshore anticyclonic circulation generate ageostrophic secondary circulation (ASC) cells due to submesoscale processes as, for example, flow interaction with the development of surface frontogenesis and nonlinear Ekman pumping. Based on observations and modeling studies, we evaluate the impact of these submesoscale processes on the formation of chlorophyll a filaments during late spring‐earlier summer, and late summer time frames. We show that during the late summer time frame, ASC leads to the development of filaments with high values of chlorophyll a concentration along the edge of the cold jet–in contrast to the earlier summer time, when the ASC mixes phytoplankton much deeper to the area below of the euphotic depth, and chlorophyll a filaments are 3–4 times weaker.